STRENGTH ANALYSIS OF A WUXI TUNNEL SHAFT USING FINITE ELEMENT METHOD - Azara Vigha Sisliana; Dedik Romahadi; Muhammad Imran (Universitas Mercu Buana, 2023)
The Wuxi Tunnel is a machine for producing mochi ice cream from China. One of the most important components in the ongoing production is the shaft. A shaft is a stationary rotating part, usually of a circular cross-section, to which elements such as gears, pulleys, cranks, sprockets, and other rotational transfer elements are attached. The load received by the shaft comes from the product and materials. The load was too heavy and worked continuously, resulting in the shaft breaking 3 times and not being straight. The purpose of this research is to analyze the shaft to determine the type of material and recommended dimensions so that the strength of the shaft is maintained and to determine the stress that occurs on the shaft due to the load from the product and other materials. The research method used in this study is the finite element method using Autodesk Inventor Pro software and manual calculations so that later, the results of the type of material and dimensions suitable for the shaft will be used. The analysis results show that the shaft can withstand loads at a diameter of 50 mm on the type of material AISI 4340 Annealed. The von Mises result for manual calculations is 294.2578 MPa, and the von Mises result for finite elements is 275.5 MPa. The allowable stress is 470 MPa. So that, AISI 4340 material with a recommended large diameter of at least 50 mm is a safe shaft limit that can be used at PT. X because the von Mises value is lower than other types of materials, and a safety factor of 1.71 is more than >1.